Determination of [11C]PBR28 Binding Potential in vivo: A First Human TSPO Blocking Study - Owen, David R; Guo, Qi; Kalk, Nicola J; Colasanti, Alessandro; Kalogiannopoulou, Dimitra; Dimber, Rahul; Lewis, Yvonne L; Libri, Vincenzo; Barletta, Julien; Ramada-Magalhaes, Joaquim; Kamalakaran, Aruloly; Nutt, David J; et al. (Journal of cerebral blood flow and metabolism, 2014)
Positron emission tomography (PET) targeting the 18 kDa translocator protein (TSPO) is used to quantify neuroinflammation. Translocator protein is expressed throughout the brain, and therefore a classical reference region approach cannot be used to estimate binding potential (BPND). Here, we used blockade of the TSPO radioligand [11C]PBR28 with the TSPO ligand XBD173, to determine the non-displaceable volume of distribution (VND), and hence estimate the BPND. A total of 26 healthy volunteers, 16 high-affinity binders (HABs) and 10 mixed affinity binders (MABs) underwent a [11C]PBR28 PET scan with arterial sampling. Six of the HABs received oral XBD173 (10 to 90 mg), 2 hours before a repeat scan. In XBD173-dosed subjects, VND was estimated via the occupancy plot. Values of BPND for all subjects were calculated using this VND estimate. Total volume of distribution (VT) of MABs (2.94 ± 0.31) was lower than VT of HABs (4.33 ± 0.29) (P<0.005). There was dose-dependent occupancy of TSPO by XBD173 (ED50 = 0.34 ± 0.13 mg/kg). The occupancy plot provided a VND estimate of 1.98 (1.69, 2.26). Based on these VND estimates, BPND for HABs is approximately twice that of MABs, consistent with predictions from in vitro data. Our estimates of [11C]PBR28 VND and hence BPND in the healthy human brain are consistent with in vitro predictions. XBD173 blockade provides a practical means of estimating VND for TSPO targeting radioligands.